Pendampingan Penggunaan Media Interaktif Zep Quiz Kepada Guru SDN Palrejo - Oktavia Istiqomah; Wardania Isnaini Aisyah; Suesthi Rhayuningsih; Achmad Rijanto; Dicki Nizar Zulfika (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
A mentoring activity on the use of the interactive media ZEP Quiz was conducted at SDN Palrejo with the primary goal of improving teachers' skills in utilizing gamification-based learning technology. The background to this activity stems from the fact that most teachers at the school are not yet familiar with or use ZEP Quiz, despite the availability of adequate digital facilities. This minimal use of technology leads to a monotonous learning process and does not facilitate active student engagement. However, in today's digital era, the implementation of innovative learning media is crucial for improving the quality of education. The methods used in this activity included initial observations, interviews with teachers, direct mentoring, and practical use of ZEP Quiz with students in class. The mentoring was designed in the form of structured training that included an introduction to the features, the creation of questions based on Bloom's Taxonomy, and strategies for integrating ZEP Quiz into learning scenarios. The results of the activity showed a significant increase in teachers' knowledge and skills. Teachers were able to operate ZEP Quiz independently, develop questions according to cognitive level, and apply them to the teaching and learning process. The implementation in the classroom received a positive response from students, characterized by high enthusiasm, active participation, and a fun, competitive atmosphere. These findings support previous research on the effectiveness of gamification in improving student motivation, engagement, and learning outcomes. In conclusion, mentoring the use of ZEP Quiz has proven effective in strengthening teacher competency while creating interactive learning that motivates students. Going forward, innovative and sustainable efforts are needed, including varying question content, developing gamification strategies, and integrating with other digital platforms, to avoid declining motivation due to the novelty effect and ensure the sustainability of technology-based learning in schools.